MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN 1-10 MELALUI MEDIA EDU-GAMES BAGI ANAK TUNAGRAHITA RINGAN - Inra - Inra (Jurnal Penelitian Pendidikan Khusus, 2012)
This study backs on the problems in the background that appears in the field, namely child lightweight X Tunagrahita SDLB class I at 20 Cottage Duo Pariaman District who have difficulty in identifying symbol number 1-10. This is evident from the beginning of the ability of children in naming the symbol numbers of children have difficulty on tests that researchers administered. children have not been able to answer all the tests correctly. This study aims to improve children's ability in identifying symbol of light Tunagrahita numbers through Edu-Games. Edu-Games is a computer software that contains games for children and full of the elements of education. Research methodology that researchers use is to research research using single subject AB design. Namely the design of a study comparing the ability to know the symbol number of children 1-10 in mild Tunagrahita X between baseline condition and the condition of the intervention. Data analysis techniques are used based on the observed data in the form of Visual Analysis of Graphs. The results are analyzed include the number of observations at baseline conditions and meeting as many as six times as much as ten times the intervention condition The results of this study can be seen in data analysis and data analysis under conditions that indicate the presence of inter-change ability to recognize the symbol on the number of children towards a better X through the medium of Edu-Games. From the analysis of data obtained can be concluded that the hypothesis (Ha) that the proposed is acceptable. Edu-Games media means to be used in improving the ability to know the symbol numbers 1-10 for kids in the class I light Tunagrahita SDLB Cottage Duo Pariaman District 20. Recommended for classroom teachers or subject teachers of Mathematics in order to use the media Edu-Games for kids Tunagrahita familiar symbol of light in the teaching of number.